2017
DOI: 10.1021/acs.langmuir.7b00934
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Foams Generated by a Rigid Surfactant Derived from Dehydroabietic Acid

Abstract: Innovation in the structure of surfactants is crucial to the construction of a surfactant-based system with intriguing properties. With dehydroabietic acid as a starting material, a nearly totally rigid azobenzene surfactant (R-azo-Na) was synthesized. The trans-R-azo-Na formed stable foams with half-lives of 636, 656, 976, and 872 min for 0.3, 1, 2, and 4 mmol·L aqueous solutions, respectively. Under UV light irradiation, a fast collapse of the foams was observed, showing an in situ response. The excellent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 66 publications
1
50
0
Order By: Relevance
“…[27] Song and co-workersr eported an absolutelyr igid surfactant (R-azo-Na) that has high foaming ability and efficient light responsiveness. [28] They also found that an anionic surfactant (C 12 biphNa) containing ab iphenyl group can form rigid nanowire-like aggregatesw ith b-CD, and hydrogels were thus obtained. [29] In our previousw ork, an ovel anionic surfactant, N-dodecylmaleimidepimaricc arboxylate (C 12 -MPA-Na, Scheme 1), synthesized from rosin, spontaneously self-assembled sequentially into large spherical micelles, annular micelles, andt hreadlike micelles with increasing concentration.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…[27] Song and co-workersr eported an absolutelyr igid surfactant (R-azo-Na) that has high foaming ability and efficient light responsiveness. [28] They also found that an anionic surfactant (C 12 biphNa) containing ab iphenyl group can form rigid nanowire-like aggregatesw ith b-CD, and hydrogels were thus obtained. [29] In our previousw ork, an ovel anionic surfactant, N-dodecylmaleimidepimaricc arboxylate (C 12 -MPA-Na, Scheme 1), synthesized from rosin, spontaneously self-assembled sequentially into large spherical micelles, annular micelles, andt hreadlike micelles with increasing concentration.…”
Section: Introductionmentioning
confidence: 96%
“…However, rigid surfactants in mixtures of catanionic surfactants have rarely been reported despite the fact that rigid surfactants have intriguing properties. It has recently been reported that surfactants with a nonplanar rigid hydrophobic group show interesting interfacial properties and unique aggregation behavior due to a strong hydrophobic effect and large molecular volume . The aromatic groups in the surfactants N10TAB and N10‐6‐10N partially overlap with the flexible alkyl chain, which prompts the formation of vesicles at quite low concentration .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, switchable surfactants have been studied extensively. Common stimuli are pH, temperature, light, magnetic field, oxidants/reductants and CO 2 . These switchable surfactants can be used to stabilize emulsion or foam which has to be demulsified or defoamed at a specific desired stage.…”
Section: Introductionmentioning
confidence: 99%